The analysis of cell received capabilities in ATM network / Norehan Abd Mutalib - Abd Mutalib, Norehan (2006)
This project presents the application of an ATM network. ATM techniques are applied in integrating digital video into broadband networks, IP internetworking and local area networks. Cell is the core of ATM networks. This project presents the measurement results on cell received in ATM traffic by configuring the Victoria equipment parameter settings for an ATM network. The testing and measurement is conducted using Victoria SDH/ATM/IP (4080C) and Victoria ATM/IP (4071C). The study focused on the cell received by the different transmission medium. Three types of transmission medium that have been tested are El (2MBits/s), E3 (34MBits/s) and STM-1 (155MBits/s). The measurement test is done according to two traffic classes which are Constant Bit Rate (CBR) and Variable Bit Rate (VBR). The test also performed Out-of-Service measurement (OOS) parameters for Cell Transfer Delay (CTD) when burst error is injected. The measurements are taken in interval time of five, 10 and 30 minutes.